A Combined Approach of RIBEM and Precise Time Integration Algorithm for Solving Transient Heat Conduction Problems - Yu, Bo; Yao, Wei-An; Gao, Xiao-Wei; Gao, Qiang (Numerical heat transfer. Part B, Fundamentals, 2014)
A combined approach of the radial integration boundary-element method (RIBEM) and the precise algorithm in the time domain is presented for solving transient heat conduction problems with heat sources. First, by expanding physical quantities at discrete time intervals, the recursive formulations of the governing equation are derived. Then, the recursive equation is solved by the RIBEM. Finally, a self-adaptive check technique is carried out to estimate how many expansion terms are needed in a time-step size. Numerical results show that the present approach can obtain satisfactory performance.